2012
DOI: 10.1016/j.reprotox.2011.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of perfluorooctane sulfonate (PFOS) and perfluorooctanoate (PFOA) and their associations with human semen quality measurements

Abstract: A total of 256 men were studied to evaluate whether serum concentrations of perfluorooctanoate (PFOA) and perfluorooctane sulfonate (PFOS) impacted semen quality or reproductive hormones. Blood and semen were collected and analyzed for perfluorochemicals and reproductive and thyroid hormones. Semen quality was assessed using standard clinical methods. Linear and logistic modeling was performed with semen profile measurements as outcomes and PFOS and PFOA in semen and plasma as explanatory variables. Adjusting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(104 citation statements)
references
References 29 publications
5
97
1
1
Order By: Relevance
“…Weak associations between PFOA and PFOS exposure and reduced fertility in humans have been observed (Fei et al, 2009;Whitworth et al, 2012). A few human studies have also shown positive but weak associations between PFOA or PFOS exposure and preeclampsia, early menopause, delayed puberty onset, and semen quality, while other studies have shown no association with some of these reproductive parameters (Fei et al, 2009;Stein et al, 2009;Knox et al, 2011;Lopez-Espinosa et al 2011;Joensen et al 2009;Raymer et al 2012;Louis et al 2013). However, a recent prospective study shows an association between in utero exposure to PFOA and semen quality and reproductive hormones in male offspring 20 years later.…”
Section: Reproductive and Developmental Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Weak associations between PFOA and PFOS exposure and reduced fertility in humans have been observed (Fei et al, 2009;Whitworth et al, 2012). A few human studies have also shown positive but weak associations between PFOA or PFOS exposure and preeclampsia, early menopause, delayed puberty onset, and semen quality, while other studies have shown no association with some of these reproductive parameters (Fei et al, 2009;Stein et al, 2009;Knox et al, 2011;Lopez-Espinosa et al 2011;Joensen et al 2009;Raymer et al 2012;Louis et al 2013). However, a recent prospective study shows an association between in utero exposure to PFOA and semen quality and reproductive hormones in male offspring 20 years later.…”
Section: Reproductive and Developmental Toxicitymentioning
confidence: 99%
“…Some studies have reported effects of PFAS exposure on thyroid, liver, glucose and lipid metabolism. Although there are some inconsistencies between the studies, exposure to PFAS, especially PFOA and PFOS, overall seems to be associated with thyroid disease, although there also seems to be some differences concerning effects in men and women (Melzer et al, 2010;Knox et al 2011;Olsen et al, 1998;Olsen et al, 2003;Olsen et al, 2012;Gallo et al, 2012). Thyroid function regulates a wide array of metabolic parameters, such as lipoprotein metabolism, and thyroid dysfunction can thus have an important effect on lipid profile and may influence the overall risk for cardiovascular disease.…”
Section: Metabolism and Thyroid Functionmentioning
confidence: 99%
“…Lowered testosterone levels and Leydig cell hyperplasia are common features among infertile men [58,59] and higher levels of PFOA and PFOS has previously been shown in infertile men [60]. On the other hand, there are also studies showing no adverse PFOA or PFOS-effects on semen parameters in neither men [41] nor rats [42]. In another study on rats given 3 mg potassium PFOS/kg body weight for 7 consecutive days, no functional alteration in the hypothalamic-pituitarythyroid axis was noted [61].Chang et al 2007 also showed that short term exposure to PFOS did not reduce thyroid hormone levels in female rats [62].…”
Section: Discussionmentioning
confidence: 92%
“…Other studies show no effect of PFAS exposure on sperm parameters [40][41][42]. Despite numerous toxicological and epidemiological studies that have examined reproductive and developmental associations [42][43][44][45][46][47], none has reported on sex ratios.…”
Section: Introductionmentioning
confidence: 97%
“…Due to the extraordinary stability of the carbon-fluorine bond, these compounds are resistant to chemical, biological and thermal degradation. Therefore, PFAAs have been found in environments and accumulate in the bodies of humans and wildlife (Giesy and Kannan, 2002;Sundström et al, 2011;Raymer et al, 2012;Houde et al, 2006). A number of studies have demonstrated the adverse effects of PFAAs on experimental animals, mostly of PFOA and PFOS (Lau et al, 2007).…”
Section: Introductionmentioning
confidence: 99%